Body mass estimation from footprint size in hominins. Issue 156 (July 2021) - Ruff, Christopher B.; Wunderlich, Roshna E.; Hatala, Kevin G.; Tuttle, Russell H.; Hilton, Charles E.; D'Août, Kristiaan; Webb, David M.; Hallgrímsson, Benedikt; Musiba, Charles; Baksh, Michael
Abstract: Although many studies relating stature to foot length have been carried out, the relationship between foot size and body mass remains poorly understood. Here we investigate this relationship in 193 adult and 50 juvenile habitually unshod/minimally shod individuals from five different populations—Machiguenga, Daasanach, Pumé, Hadzabe, and Samoans—varying greatly in body size and shape. Body mass is highly correlated with foot size, and can be predicted from foot area (maximum length × breadth) in the combined sample with an average error of about 10%. However, comparisons among populations indicate that body shape, as represented by the body mass index (BMI), has a significant effect on foot size proportions, with higher BMI samples exhibiting relatively smaller feet. Thus, we also derive equations for estimating body mass from both foot size and BMI, with BMI in footprint samples taken as an average value for a taxon or population, estimated independently from skeletal remains. Techniques are also developed for estimating body mass in juveniles, who have relatively larger feet than adults, and for converting between foot and footprint size. Sample applications are given for five Pliocene through Holocene hominin footprint samples from Laetoli ( Australopithecus afarensis ), Ileret (probable Homo erectus ), Happisburgh (possible Homo antecessor ), Le Rozel (archaic Homo sapiens ), and Barcin Höyük ( H. sapiens ). Body mass estimates for Homo footprint samples appear reasonable when compared to skeletal estimates for related samples. However, estimates for the Laetoli footprint sample using the new formulae appear to be too high when compared to skeletal estimates for A. afarensis . Based on the proportions of A.L. 288-1, this is apparently a result of relatively large feet in this taxon. A different method using a ratio between body mass and foot area in A.L. 288-1 provides estimates more concordant with skeletal estimates and should be used for A. afarensis .